Predictive Factors for Complete Response and Recurrence after Transarterial Chemoembolization in Hepatocellular Carcinoma - Jeong, Shin Ok; Kim, Eui Bae; Jeong, Soung Won; Jang, Jae Young; Lee, Sae Hwan; Kim, Sang Gyune; Cha, Sang Woo; Kim, Young Seok; Cho, Young Deok; Kim, Hong Soo; Kim, Boo Sung; Kim, Yong Jae; et al. (Gut and liver, 2017)
To investigate the predictive factors for complete response (CR) and recurrence after CR in patients with hepatocellular carcinoma (HCC) treated with transarterial chemoembolization (TACE). Among 691 newly diagnosed HCC patients, 287 were treated with TACE as a first therapy. We analyzed the predictive factors for CR, recurrence after CR, and overall survival (OS). Eighty-one patients (28.2%) achieved CR after TACE, and recurrence after CR was detected in 35 patients (43.2%). In multivariate analyses, tumor size (≤5 cm) and single nodularity were predictive factors for CR, with hazard ratios (HRs) of 0.35 (p=0.002) and 0.41 (p<0.001), respectively. Elevated serum α-fetoprotein (AFP) (>20 ng/mL) level and multinodularity exhibited significant relationships with recurrence after CR, with HRs of 2.220 (p=0.026) and 3.887 (p<0.001), respectively. Tumor size (>5 cm), multinodularity, elevated serum AFP (>20 ng/mL) level, Child-Turcotte-Pugh score (B and C), and portal vein thrombosis were significant factors for OS. In patients treated with TACE as a first therapy, tumor size (≤5 cm) and single nodularity were predictive factors for CR, and multinodularity and elevated serum AFP (>20 ng/mL) levels were predictive factors for recurrence after CR. These factors were also significant for OS.